A study on the adsorption properties of multiwalled carbon nanotubes and their relationship to applications as volatile organic compounds sensors / Nurul Rozullyah Zulkepely - Nurul Rozullyah, Zulkepely (2018)
In this thesis, a study on the diameter effect of the adsorption properties of Rhodamine 6G on multiwalled carbon nanotubes is presented. Multiwalled carbon nanotubes with diameters between 8 to 50 nm were used. Rhodamine 6G adsorption properties were measured based on the time variation of concentration reduction and were fitted to the Langmuir, Freundlich and Temkin adsorption models. The values of maximum adsorption capacity obtained from Langmuir isotherm equation at 300 K were 222 mg/g for ~8 nm and 49.3 mg/g for ~50 nm MWCNTs. Based on the Freundlich model, the constant for adsorption capacity for Rhodamine 6G were 146.59 mg/g and 19.70 mg/g for MWCNTs for diameter ~8 and ~50 nm, respectively. The difference indicated strong interaction of the dye molecules with the smaller diameter MWCNTs. Also, based on all the models, it can be concluded the smallest diameter was the better adsorbent compared to the large diameter MWCNTs for the adsorption of R6G since it was related with the high specific surface area. Kinetic analysis of the time variation of the R6G concentration towards different amounts of MWCNTs were modeled to the pseudo first and the second order equations and shown that the adsorption kinetic was more accurately represented by a pseudo second-order model with regression value of pseudo second-order > first-order model. For vapor sensor, pure MWCNTs (diameters = ~8, 20-30 and ~50 nm) together with ZnO decorated with MWCNTs (diameter = ~50 nm) was used as sensor fabricated on printing paper for ethanol and toluene vapor sensing. The resistance of the MWCNTs samples on printing paper were 2.06, 0.49 and 0.30 kΩ for MWCNTs for diameters ~8, 20-30 and ~50 nm respectively. The sensing response measured by exposing the samples to toluene vapor at concentrations of between 425 and 4253 ppm yielded sensitivities of 12.73 × 10-5, 7.69 × 10-5 and 2.65 × 10-5 ppm-1 while for ethanol vapor at concentrations of between 780 and 7804 ppm were 9.88 × 10-5, 4.39 × 10-5, and 2.88 × 10-5 ppm-1 for MWCNTs for diameters ~8, 20-30 and ~50 nm respectively. High sensitivity for low diameters can be due to higher effective specific surface area afforded higher conductivity by the MWCNTs with smaller diameter.